2014
DOI: 10.1057/ejis.2013.19
|View full text |Cite
|
Sign up to set email alerts
|

Internet adoption by the elderly: employing IS technology acceptance theories for understanding the age-related digital divide

Abstract: Information technology (IT) allows members of the growing elderly population to remain independent longer. However, while technology becomes more and more pervasive, an age-related underutilisation of IT remains observable. For instance, elderly people (65 years of age and older) are significantly less likely to use the Internet than the average population (see, for instance, European Commission, 2011). This age-related digital divide prevents many elderly people from using IT to enhance their quality of life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
243
1
30

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(289 citation statements)
references
References 70 publications
15
243
1
30
Order By: Relevance
“…-"Performance Expectancy" is the most moderated factor by education then "Facilitating conditions", "Social influence" and "Design issues" being neutral to education. (Niehaves & Plattfaut, 2014) Aim: Internet adoption by the elderly (65+) based on modified UTAUT model. Methods: Literature review survey +interviews (150 resp.)…”
Section: Research Methodology and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…-"Performance Expectancy" is the most moderated factor by education then "Facilitating conditions", "Social influence" and "Design issues" being neutral to education. (Niehaves & Plattfaut, 2014) Aim: Internet adoption by the elderly (65+) based on modified UTAUT model. Methods: Literature review survey +interviews (150 resp.)…”
Section: Research Methodology and Resultsmentioning
confidence: 99%
“…Most of the analysed papers conclude that the level of education has a significant influence on the acceptance of digital technology by the elderly: persons with higher education HE are 3.1 times more likely to use a PC as those with a lower educational level (Heart & Kalderon, 2013), HE senior using Internet have rates exceeding the general population (Fischer, David, & et al, 2014), (Nayak, Priest, & White, 2010) and (Niehaves & Plattfaut, 2014). (Berry, 2011) even declares that the education level should be incorporated as a map of reasons for digital exclusion.…”
Section: Influence Of Education Level On Elderly Acceptance Of Digitamentioning
confidence: 99%
See 1 more Smart Citation
“…However, unlike those in conventional universities who share a more homogeneous age range, ODL students often comprise of working adults with more diverse age groups. In such cases, the age factor has been identified as a barrier to technology adoption, whereby older individuals are often less receptive towards technology compared to younger persons who place a higher emphasis on the extrinsic values of technology uptake (Claar, Dias and Shields 2014;Niehaves and Plattfaut 2014;van Deursen and van Dijk 2014). Hence, it is hypothesised that older (young) individuals may be less (more) likely to indulge in e-resource usage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, given our focus on individuals' health factors, we neglected other variables that might account for health information usage. In this respect, further research could examine the influence of individual IT-related factors, such as computer selfefficacy, computer anxiety, or Personal Innovativeness in IT, which have been found to be important factors of older adults' IT behavior [26,35,65,66]. Organizational research revolving around exploratory IT behavior has shown that environmental factors can stimulate employees' attempts to find novel purposes for the target system.…”
Section: Limitations and Further Researchmentioning
confidence: 99%